The identification and management of the profunda femoris artery as a rare source of a late type II endoleak - Paul Ghaly, MBBS, MS; Kejia Wang, MBBS; Delfino Di Mascio, BSc (Med), MBBS (UNSW), FRACS (Vascular); Luke Baker, MBBS, FRANZCR, FACP, EBIR; Mauro Vicaretti, MBBS (Sydney), PhD (Sydney), FRACS (Vascular) (Journal of Vascular Surgery Cases and Innovative Techniques, 2021)
Internal iliac artery aneurysms are found in 20% of abdominal aortic aneurysm cases, with a high mortality rate in the event of rupture. Type II endoleaks are a common complication after endovascular intervention. Transarterial or direct sac puncture techniques have superseded open surgical repair due to the challenging nature open surgery presents in accessing the feeding vessel(s). We describe the rare source of a late type II endoleak feeding from the profunda femoris in an 83-year-old man after fenestrated endovascular aortic aneurysm repair and concurrent embolization of the right internal iliac artery for treatment of a juxtarenal abdominal aortic aneurysm and internal iliac artery aneurysm.